Предмет: Алгебра,
автор: lizasm13
Разложить на множители : 4а^2*b^2(a^2+b^2)-(a^2+b^2)^3
Ответы
Автор ответа:
0
4а²b²(a² + b²) - (a² + b²)³ = (a² + b²)(4a²b² - (a² + b²)²) = (a² + b²)(4a²b² - a⁴ - 2a²b² - b⁴) = (a² + b²)( -a⁴ + 2a²b² - b⁴) = - (a² + b²)(a⁴ - 2a²b² + b⁴) = - (a² + b²)(a² - b²)² = -(a² + b²)(a - b)²(a + b)²
Похожие вопросы
Предмет: История,
автор: слвоапмр
Предмет: Геометрия,
автор: marijjjj16
Предмет: История,
автор: senanastasia12
Предмет: Физика,
автор: natashalvinova
Предмет: Математика,
автор: рауан6исмуханов